Several strains of Echinococcus granulosus infect livestock and humans in Argentina - Kamenetzky, Laura (2002)
Fil: Kamenetzky, Laura. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina.